Decreased Mortality After Establishing a Pediatric Emergency Unit at an Urban Referral Hospital in Ghana. Issue 7 (July 2021) - Sylverken, Justice; Robison, Jeff A.; Osei-Akoto, Alex; Nguah, Samuel Blay; Addo-Yobo, Emmanuel; Balch, Alfred; Bolte, Robert; Ansong, Daniel
Abstract : Abstract: Emergently ill infants and children are often inadequately recognized and stabilized by health care facilities in low- and middle-income countries. Limited reports have shown that process improvements and prioritization of emergency care for children presenting to the hospital can improve pediatric hospital mortality. A dedicated pediatric emergency unit (PEU) was established for nontrauma emergencies at a busy teaching and referral hospital in Kumasi, Ghana, in response to high inpatient mortality early during hospitalization. The PEU was designed to identify and separate critically ill children from more stable children on admission. Locally available hospital resources were reallocated from other areas of the hospital to prioritize staffing and supplies for the PEU. A multiyear data set of nonnewborn inpatient mortality was analyzed with a change point model to find the point at which mortality changed the most within the Department of Child Health or the maximum likelihood estimate. Relative risk of mortality for the periods 1 and 2 years immediately before and after the implementation of the PEU and each individual year compared with its preceding year was analyzed to further establish a temporal correlation of changes in mortality rates to the PEU implementation. Individual years were also analyzed against preimplementation data to establish the durability of mortality improvements. Patient mortality decreased over the analyzed period with the maximum change point strongly associated with implementation of the PEU. Relative risk values of mortality 1 year and 2 years immediately before and after implementation of the PEU were 0.70 (0.62–0.78) and 0.69 (0.64–0.74) respectively, representing a one-third reduction in mortality. The only other mortality improvements seen in the year-to-year analysis were between July 2004–June 2005 compared with July 2005–June 2006 with a relative risk of 0.86 (0.77–0.96). Prioritizing and redirecting limited resources toward pediatric emergency care in low- and middle-income country hospitals is associated with reductions in inpatient mortality that are both immediate and sustained.